2018
DOI: 10.1038/s41598-018-28427-5
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α regulates COXIV subunits, a potential mechanism of self-protective response to microwave induced mitochondrial damages in neurons

Abstract: Anxiety and speculation about potential health hazards of microwaves exposure are spreading in the past decades. Hypoxia-inducible factor-1α (HIF-1α), which can be activated by reactive oxygen species (ROS), played pivotal roles in protective responses against microwave in neuron-like cells. In this study, we established 30 mW/cm2 microwave exposed animal model, which could result in revisable injuries of neuronal mitochondria, including ultrastructure and functions, such as ROS generation and cytochrome c oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Through bioinformatics analysis, we predicted the target genes of miR-30a that may be involved in autophagy regulation, including Beclin1, Prkaa2, Irs1, Pik3r2, Rras2, Ddit4, Gabarapl2 and Atg12. The results of our previous study demonstrated that microwave radiation induces abnormal energy metabolism in hippocampal neurons and neuron-like cells [30,31]. In the present study, we showed that microwave radiation activates AMPK signaling, acellular energy sensor, in both rat hippocampi and neuron-like cells.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Through bioinformatics analysis, we predicted the target genes of miR-30a that may be involved in autophagy regulation, including Beclin1, Prkaa2, Irs1, Pik3r2, Rras2, Ddit4, Gabarapl2 and Atg12. The results of our previous study demonstrated that microwave radiation induces abnormal energy metabolism in hippocampal neurons and neuron-like cells [30,31]. In the present study, we showed that microwave radiation activates AMPK signaling, acellular energy sensor, in both rat hippocampi and neuron-like cells.…”
Section: Discussionsupporting
confidence: 64%
“…4C). We previously showed that microwave radiation can induce abnormal energy metabolism in hippocampal neurons and neuron-like cells [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is required for the maturation of several proteins involved in mitochondrial gene expression (SLIRP, MTERFD3 and FASTKD2), mtDNA replication (SSBP) and the ATP-dependent mitoprotease CLPX (Zurita Rendón andShoubridge, 2018, Lagouge et al, 2015) (Figure 3, mtDNA expression). Finally, it degrades COX4-1 under hypoxic conditions to promote the assembly of COX4-2, a structural subunit of the terminal electron transport chain (ETC) enzyme cytochrome c oxidase, thereby optimizing electron transfer and oxygen consumption (Hao et al, 2018) (Figure 3, OXPHOS complexes). Given the crucial role of LONP1 in mitochondrial function, it is not surprising that patients harboring mutations in LONP1 exhibit OXPHOS deficiencies observed in other mitochondrial diseases (Peter et al, 2018).…”
Section: Mitochondrial Proteasesmentioning
confidence: 99%
“…Moreover, the transformation of LC3 from LC3I to LC3II is the pivotal step of mitophagosome formation, and LC3II content reflects straightway the amount of mitophagosomes (50). Cytochrome c oxidase (COX) subunits, complex IV in the mitochondrial respiratory chain, are located in the inner mitochondrial membrane (51). In our research, treatment with Mo and/or Cd enhanced the co-localization of COX IV-labeled mitochondria with LC3.…”
Section: Discussionmentioning
confidence: 56%